Strategic Planning of Regional Tourism Information System of Morotai Island Regency using Ward and Peppard Framework - Eko Widodo; Yerik Afrianto Singgalen (Journal of Information System and Informatics, 2022)
The tourism development program in Indonesia is not central but decentralized so that each autonomous region has the authority to determine the direction of policies and strategies for developing tourism potential in their respective areas. In the context of the Morotai Islands regency, an integrated regional tourism information system has not been designed to control and synchronize stakeholders' interests and optimize the marketing of regional tourist destinations. Considering this, this study offers the Ward and Peppard framework for the strategic design of Sistem Informasi Pariwisata Daerah (SIPARDA) as a website-based application that can be used for data collection and monitoring of regional tourism resources as well as tourism destination development programs in Morotai Island Regency. This study shows that the identification of external and internal conditions of the business environment is not limited to the Value Chain approach and Porter's Five Forces Model but also the Tourism Area Life Cycle and Irritation Index to understand the context of regional tourism-related to tourism resources both attractions, accommodation, amenities, and accessibility, as well as the level of acceptance of the Morotai people towards tourism development programs. Furthermore, identifying the current internal and external conditions of information systems or information technology in the portfolio application is analyzed based on Strenght, Weaknesses, Opportunities, and Threats (SWOT) to provide recommendations for future application portfolios. The results of this study recommend the Regional Tourism Information System known as Sistem Informasi Pariwisata Daerah (SIPARDA) as a portfolio future application that needs to be prioritized to optimize the function of monitoring tourism development in the Morotai Island Regency.